Cosolvent fractionation of PMOXA-b-PDMS-b-PMOXA: Bulk separation of triblocks from multiblocks. (March 2017) - Lörcher, Samuel; Meier, Wolfgang
Graphical abstract: Highlights: Cosolvent fractionation (CSF) - an important step for polymersome assembly. CSF allows the separation of PMOXA-PDMS-PMOXA triblocks from multiblocks. Commercial PDMS was fractioned to decrease Ð from ∼1.9 to ∼1.2. Abstract: Challenges regarding the synthesis, purification, and characterization of the amphiphilic triblock copolymer poly(2-methyl-2-oxazoline)- block -polydimethylsiloxane- block -poly(2-methyl-2-oxazoline) (PMOXA- b -PDMS- b -PMOXA) are herein illustrated and discussed. A block copolymer (BCP) library was synthesised by cationic ring-opening polymerisation of 2-methyl-2-oxazoline on broadly and narrowly dispersed PDMS macroinitiators. The crude BCPs were fractioned by a newly developed cosolvent fractionation technique. With this it is possible to remove the side products of chain-transfer reactions, intrinsic to the polymerisation of 2-oxazolines. The obtained fractions were characterized by nuclear magnetic resonance, gel permeation chromatography and light scattering, revealing that the cosolvent fractionation separates multiblock copolymers from triblock copolymers. Self-assembly of the individual polymer fractions showed that the cosolvent fractionation is essential to yield polymersome forming triblock copolymers.